(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Albar H, Juhriah, Santosa S. 2025. Ethnobotany of medicinal plants by the community in Langgudu Sub-district, Bima District, West Nusa Tenggara, Indonesia. Biodiversitas 26: 315-325. The use of plants as traditional medicine has been a long-standing practice among the people of Langgudu Sub-district, Bima District, West Nusa Tenggara, Indonesia. This study aims to determine the diversity of medicinal plant species, plant parts used, processing methods, and how to use plants as traditional medicine. This study uses a qualitative and quantitative descriptive approach. Data collection using a semi-structured questionnaire was distributed to 45 respondents who are traditional healers and community users of medicinal plants. Questionnaire data with respondents were analyzed using quantitative ethnobotany index calculations consisting of Use Value (UV), Fidelity Level (FL), and Informant Consensus Factor (ICF). Based on the results of the study, the community uses 50 species of medicinal plants classified into 44 genera and 29 families as traditional medicine to treat 37 different types of diseases. The largest families come from the Fabaceae, Moraceae, and Zingiberaceae families (8% each). The most widely used part of the plant is the leaves (44%). The most common processing method is boiling (52%), at the same time, the most common way of use is drinking (76%). The highest UV values were found in the plant species Carica papaya, Strychnos nux-vomica, Swietenia mahagoni, Psidium guajava, and Curcuma longa, with values of 1 each. The highest FL value was found in the P. guajava plant with a value of (100%), which is the type of plant with the largest number of user respondents. The highest ICF values were found in the categories of dermatological diseases and reproductive system disorders, with values of 0.96 each. Medical plants play a very important role in providing health services in the study area. This study needs to be carried out scientifically related to its utilization and safety through various biological activity tests and toxicological properties.